Dorsal Hump Reduction Based on the New Ethmoidal Point Classification: A Clinical and Radiological Study of the Keystone Area in 138 Patients. (30th January 2020) - Ferreira, Miguel Gonçalves; Dias, David Rodrigues; Cardoso, Luis; Santos, Mariline; Sousa, Cecília A; Dourado, Nuno; Santos, Jorge; Amarante, José
Abstract: Background: Hump resection often requires reorganization of the keystone area. Objectives: The authors sought to describe the importance of the point where the perpendicular plate of ethmoid joins the septal cartilage (SC) and the nasal bones (NB) (Ethmoidal point [E-point]) for hump resection surgical planning. Methods: Measurements from mid-sagittal slices in nasal computed tomography scans taken in adult Caucasian patients between January 2015 and December 2018 were compared between patients seeking primary rhinoplasty due to a nasal hump and patients not seeking rhinoplasty (control group). Patients with previous nasal surgery or trauma, genetic or congenital facial disorders, and high septal deviation were excluded. The length of overlap between NB and SC was compared between the 2 groups. The location of the E-point in relation to the beginning of the nasal hump in the cephalocaudal direction was documented in the patients seeking rhinoplasty. Results: The study population included 138 patients, 69 seeking and 69 not seeking rhinoplasty (96 females). The mean age was 32.9 years (range, 18-55 years). The length of overlap between NB and SC was similar between both groups (11.7 ± 3.3 vs 10.8 ± 3.3; P  = 0.235). The E-point was located before the beginning of the nasal hump in 97% (67/69) of nasal hump patients, and it could be found a mean distance of 2.3 (±2.3) mm cephalic to the latter. Conclusions: As a rule, the perpendicular plate of the ethmoid does not contribute to the nasal hump; therefore, only in exceptional cases should this be addressed while performing dorsal reduction. Level of Evidence: 3: